Parameter Estimation STAR (1;1) Model Using Binary Weight - Khafsah Joebaedi; Iin Irianingsih; Badrulfalah Badrulfalah; Dwi Susanti; Kankan Parmikanti (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2019)
Space Time Auto Regressive(1;1) Model or STAR(1;1) model is a form of model that involves location and time. The STAR(1;1) model is a stationary space time model in mean and variance. The STAR model can be used to forecast future observations at these locations by involving the effects of observations at other nearby locations in spatial lag 1 and lag time 1 [2]. The STAR model can be written as a linear model assuming that error is normally distributed with zero mean and constant variance. In this research, the parameter estimation procedure for STAR model using binary weight, MKT method and STAR model for the estimation of petroleum production in 3 wells is assumed to be in a homogeneous reservoir.